Interferensi Bahasa Indonesia Terhadap Bahasa Sunda Pada Podcast Sule Production - Sihombing, Kristi Anastasya; Emha, Ratna Juwitasari (STKIP Singkawang, 2024)
This study explains the interference in phonology and morphology that occurs on the Sule Production podcast on youtube. This research is a qualitative type of research. The data and data sources are in the form of Ariel's speech as a resource person in a podcast hosted by Sule on the Sule Production Youtube channel entitled